2022
DOI: 10.21037/apm-21-3171
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mecobalamin combined with vestibular rehabilitation training for acute vestibular neuritis: a systematic review and meta-analysis

Abstract: Background: This study aimed to investigate the efficacy and safety of mecobalamin combined with vestibular rehabilitation training in acute vestibular neuritis and to improve the clinical therapeutic effect in vestibular nerve disease. Methods:We performed a literature search of the PubMed, Medline, China National Knowledge Infrastructure (CNKI), and other databases from the date of establishment of the database until the present.The search terms included "mecobalamin", "vestibular rehabilitation training", "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The results suggest that this combination is more effective in treating patients with sudden sensorineural hearing loss than methylcobalamin treatment alone. This could be due to the stimulation of catecholamine release, further generating endothelial relaxation factors, leading to vasodilation and improved blood circulation [18]. Simultaneously, the combined use of holistic copper acupuncture and scraping technique can promote the utilization of glucose and oxygen in ischemic tissues, accelerate local microcirculation, and improve inner ear microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that this combination is more effective in treating patients with sudden sensorineural hearing loss than methylcobalamin treatment alone. This could be due to the stimulation of catecholamine release, further generating endothelial relaxation factors, leading to vasodilation and improved blood circulation [18]. Simultaneously, the combined use of holistic copper acupuncture and scraping technique can promote the utilization of glucose and oxygen in ischemic tissues, accelerate local microcirculation, and improve inner ear microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Romberg's test: Postural stability during quiet standing was evaluated with patients in various conditions, including eyes open and closed. Deviations from the expected postural stability were noted [23].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…By analyzing the kinematics of these movements, ultrasound craniocorpography can provide insightful data on the dynamics of the vestibulospinal reflex and its relationship to postural control. However, it is important to note that each testing method has its unique advantages and limitations, necessitating careful consideration when selecting the appropriate assessment strategy based on the clinical scenario [23].…”
mentioning
confidence: 99%
“…And whether to combine steroid drugs with VRT is an issue that needs to be considered. Most recently, Huang et al (28) compared steroid drugs combined with VRT as an intervention method in the experimental group with steroid drugs in the control group, and the outcome indicators included DHI score, caloric lateralization and VEMPs. It was concluded that steroid drugs combined with VRT was more effective than steroid alone.…”
Section: Introductionmentioning
confidence: 99%